Strategies to improve artificial insemination by donor - Dyer, Silke Juliane (Department of Obstetrics and Gynaecology, 2017)
Artificial insemination with donor sperm is a widely accepted form of treatment for severe male factor infertility. The introduction of quarantined, cryopreserved semen and the associated reduction in cycle fecundity when compared to fresh semen necessitated the development of strategies to improve the performance of frozen sperm. A prospective randomised clinical trail was undertaken in the Reproductive Medicine Unit at Groote Schuur Hospital to compare intrauterine insemination with intracervical insemination in a therapeutic donor insemination program with cryopreserved semen. The method of insemination was alternated in successive cycles in each patient after intitial randomised selection. Forty three patients underwent 61 intracervical insemination cycles and 48 intrauterine insemination cycles. Strict cycle control was exercised and the timing and frequency of insemination followed a specific protocol. Eighteen clinical pregnancies occurred following eleven intrauterine insemination cycles (22.9% per cycle) and seven intracervical insemination cycles (11.5% per cycle). Treatment outcome was influenced by patient age, the severity of the male factor and endometriosis. Most pregnancies followed insemination with 15 to 25 million motile sperm. Sperm fecundity differed amongst donors. The findings of our study and the current literature suggest that intrauterine insemination improves cycle fecundity in therapeutic donor insemination cycles with frozen donor sperm.